Special purpose entities and bank loan contracting - Kim, Jeong-Bon; Song, Byron Y.; Wang, Zheng (Journal of Banking & Finance, 2017)
In this study, we show that a firm's use of special purpose entities (SPEs) is associated with unfavorable loan contract terms, including higher loan rates, collateral requirements, and restrictive covenants. Further analyses suggest that the association between the use of SPEs and unfavorable loan contract terms is primarily due to the increase in the information risk faced by lenders, as firm managers can easily use SPEs to manipulate earnings and hide losses. Specifically, we find that the use of SPEs has a more pronounced effect on increasing the cost of loans and causing more stringent non-price loan terms when managers have a stronger incentive to manipulate earnings and when banks have less knowledge about the SPE sponsor firms due to the lack of prior lending relationship. In addition, we find that the use of SPEs is associated with a greater likelihood of accounting restatements and greater information asymmetry between inside managers and outside capital suppliers.